Regulation of Customary Law Communities' Ulayat Rights in Indonesia - Umami, Allan Mustafa; Alqindy, Fatria Hikmatiar (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Customary law community customary rights are the right to manage customary land. Customary land is land that is occupied, managed, passed down from each generation of customary law communities who have a connection to the realm of spirituality. Customary land is very important, not only valuable materially, but non-materially or in terms of spiritual relationships. The existence of customary rights is recognized by the highest regulations in Indonesia, however, in lower regulations, customary rights must obey and submit to government rules and policies. Since the promulgation of Law Number 5 of 1960 concerning Basic Agrarian Principles (UUPA) it should be the basis for recognizing customary rights. The provisions of the articles in the UUPA do not regulate in detail regarding customary rights, resulting in the dynamic formation of legislation in the land sector and related matters. The formulation of the problem in this research is how are the customary law communities' customary rights regulated in Indonesia? The research method used in this research is normative legal research, namely a statutory approach and a conceptual approach.